Enterprise Surveys : Serbia Country Profile 2013 - World Bank; International Finance Corporation (Washington, DC, 2014)
The enterprise surveys focus on the many factors that shape the business environment. The qualitative and quantitative data collected through the surveys connect a country s business environment characteristics with firm productivity and performance. The country profile for Serbia is based on data from the enterprise surveys conducted by the World Bank. The benchmarks include the averages for the group of countries in Eastern Europe and Central Asia and the Serbia income group. The country profiles provide an overview of key business environment indicators in each country, comparing them to their respective geographic region and group of countries with similar incomes. Breakdowns by firm size are presented in the appendix with all indicators used to make the graphs.